Evaluation of terrestrial carbonaceous matter aromatization by Raman spectroscopy and its application to C chondrites. (30th March 2020) - Schmidt, Jaques S.; Hinrichs, Ruth
Abstract: A Raman method to estimate the aromatization degree of carbonaceous matter (CM) was established, and calibrated by literature data respecting differences in acquisition procedures. The generated equations allowed a comparison of the G‐band width to vitrinite reflectance, and to additional structural organization parameter extracted from X‐ray powder diffraction. The relations between aromatization degree and peak temperatures from literature were then propagated to G‐band width parameter. The applicability of these geothermometers is demonstrated by the consistency of data obtained for carbonaceous chondrites with previous estimations. Since the CM aromatization is controlled by peak temperature and time span, it is possible to estimate the duration of chondrite's heating events. The G‐band width relation to elemental ratio trends of organic matter in chondrites, interplanetary dust particles, glucose, and saccharose‐based semi‐coke favors synthesis by formose route. These findings provide new approaches for the future development of chemical kinetic models for organic matter of chondrites. A reliable chemical model may allow the external calibration of numerical models for accurately evaluating the peak temperatures and cooling durations of chondrites.